$\unicode[STIX]{x1D711}$-CONTRACTIBILITY AND $\unicode[STIX]{x1D711}$-CONNES AMENABILITY COINCIDE WITH SOME OLDER NOTIONS. Issue 2 (30th January 2018) - MAHMOODI, AMIN
Abstract : It is shown that various definitions of $\unicode[STIX]{x1D711}$ -Connes amenability and $\unicode[STIX]{x1D711}$ -contractibility are equivalent to older and simpler concepts.